Red Blood Cell Transfusions Affect Intestinal and Cerebral Oxygenation Differently in Preterm Infants with and without Subsequent Necrotizing Enterocolitis - Kalteren, Willemien S.; Kuik, Sara J.; Van Braeckel, Koenraad N. J. A.; Hulscher, Jan B. F.; Bos, Arend F.; Kooi, Elisabeth M. W.; van der Laan, Michelle E. (American Journal of Perinatology, 2018)
Objective To assess intestinal and cerebral oxygenation during and after red blood cell (RBC) transfusions in preterms with or without subsequent transfusion-associated necrotizing enterocolitis (TANEC).Study Design In preterms of < 32 weeks' gestational age, we measured intestinal and cerebral regional tissue oxygen saturation (rintSO2, rcSO2) and their variabilities using near-infrared spectroscopy during and after transfusions. We compared eight infants who developed TANEC 6 to 48 hours after RBC transfusions with 16 controls.Results In TANEC infants, rcSO2 was lower during and after RBC transfusions than in controls, median (interquartile range) 55% (50–62) versus 72% (65–75), p < 0.01. There were no differences regarding rintSO2. Individual rintSO2 and rcSO2 ranges were smaller after transfusions in TANEC infants, 28% (9–36) versus 49% (40–65), p < 0.01, and 17% (14–33) versus 36% (26–57), p = 0.01, as was short-term rintSO2 variability. For each 10% higher rcSO2, the risk of developing TANEC decreased (odds ratio 0.09; 95% confidence interval 0.01–0.63). The smaller the rintSO2 range after transfusion, the higher the risk of developing TANEC.Conclusion In preterm infants lower rcSO2, but not rintSO2, values during and after RBC transfusions are associated with TANEC. Lower rintSO2 and rcSO2 variabilities after RBC transfusions may represent a diminished capacity for vascular adaptation, possibly leading to TANEC.
Keywords: red blood cell transfusion; intestinal regional tissue oxygen saturation; cerebral regional tissue oxygen saturation; necrotizing enterocolitis; preterm infants; variability; hemoglobin; near-infrared spectroscopy